Pengaruh Gaya Kepemimpinan, Kompetensi, dan Motivasi Kerja Dosen terhadap Kinerja Dosen FKIP di Universitas Simalungun Pematangsiantar - Rukayah Noprilan Siagian (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This research aims to find out the picture and influence of leadership style, competence and motivation of lecturer work at FKIP Universitas Simalungun simultaneously and partially. Leadership style has a vital role in supporting and improving lecturer performance. High competence will improve performance. High work motivation will also improve the performance of lecturers in carrying out their duties and obligations. This research uses quantitative methods. The sample in this study was 42 lecturer at Universitas Simalungun. The analysis method used is the Multiple Linear Regression model. The data in this study is primary data collected using questionnaires. The analysis method used is Multiple Linear Regression. To test hypotheses simultaneously, F-test is used and partially used t-test.